Education choices in Ethiopia. - Woldehanna, T; Mekonnen, A; Jones, N; Tefera, B; Seager, J; Alemu, T; Asgedom, G (Young Lives (Project), DFID (University of Oxford), 2005)
This paper investigates the link between micro-level outcomes and macro-level policy initiatives for a sample of eight-year-old children in Ethiopia. It uses school enrolment data from a 2002 survey of 1,000 rural and urban households from food insecure communities. This study investigated external factors associated with children’s enrolment in school, such as lack of income, labour, economic shocks, social capital and education of adults in the household. We found that household wealth, cognitive social capital (defined as perceived levels of trust and reciprocity), adult education levels, and ownership of land had a positive impact on whether eight-year-old children were attending school. Household wealth had the strongest impact followed by cognitive social capital, the maximum level of education attained by female adults in the household, ownership or rental or land, and the maximum level of education attained by male adults in the household. In contrast, child enrolment was found to be negatively associated with the number of household members over the age of 15, birth order, ownership of livestock, economic shocks experienced, distance to primary school and child labour, in declining magnitude. The findings in general suggest that increasing child enrolment in primary school – a key aspiration of Ethiopia’s Sustainable Development and Poverty Reduction Programme and its Education Sector Development Programme – requires education policies to address regional, gender and wealth disparities. Education programmes are also needed for adults who take care of children. Broader inter-sectoral policies are needed to ensure that policies relating to credit, labour and infrastructure facilitate rather than hinder children’s education.